Karakteristik Pengeringan dan Efisiensi Energi Alat Pengering Kopra Tipe Rak Berbahan Bakar Biomassa - Sugeng Triyono; Agus Haryanto; Udin Hasanudin; Ribut Sugiharto (abe.fp.unila.ac.id, 2026)
Copra quality is strongly influenced by the drying process. Traditional sun drying and smoking methods often require a long drying time and may produce low-quality copra. This study aimed to design and evaluate the performance of a biomass-fueled tray-type copra dryer. The dryer consisted of two drying chambers separated by a heat-exchange tunnel equipped with heat-retaining fins and operated using either wood or coconut shell as fuel. Performance evaluation was conducted under full-load conditions in Pagelaran Village, Lampung, by observing temperature distribution, moisture reduction, drying rate, fuel consumption, energy efficiency, and drying characteristics. The results showed that the developed dryer operated satisfactorily and was capable of producing high-quality copra. The use of coconut shell resulted in better drying performance than wood. Drying temperatures ranged from 54 to 66°C and provided favorable conditions for moisture removal. The dryer accommodated approximately 278 coconuts (about 160 kg fresh coconut meat) and produced around 60 kg of dried copra. The drying rate reached 2.41 kg H₂O h⁻¹ (3.73% dry basis h⁻¹), with fuel consumption of 54.46 kg and an energy efficiency of 6.51%. Moisture ratio decreased exponentially with drying time, indicating effective moisture removal throughout the drying process. In addition, the dryer produced bright-colored copra without signs of scorching. The utilization of coconut shell as fuel also demonstrates the potential use of coconut biomass residues as a sustainable energy source for small-scale copra processing.